Electric welding technologies in minimally invasive thoracic surgery - Kirilyuk, A. A. (Journal of Education, Health and Sport, 2017)
Introduction of suture less electro sealing technologies, made its wide use in non-invasive thoracic surgery. Most important use of these methods was seen in performing video thoracoscopic lung resections (VTLR). The aim of the work - to access possibilities of different methods of electro sealing VTLR. Videothoracoscopic wedge resection was performed in 142 patients with different surgical pathologies of chest. Out of which 103 operations were closed methods and 39 were video-assisted. Suture less VTLR were performed with the use of electro sealing complexes: EK- 300M1, “LigaSure Valleylab” and electrosurgical instruments. Few patients with suture less methods were additionally sealed with mechanical sutures by using end staplers and traditional stitching apparatus. All the examined patient were discharged from the hospital. Average hospital stay was 7.8 days. Complications were seen in 7.7% cases. Lethality was not registered. High efficiency of VTLR for the diagnosis and treatment of solitary and disseminated lung processes of unknown etiologist and pneumothorax. No evidence in the results and effectiveness of EK 300M1 and LigaSure Valleylab in closed and video assisted methods. Criteria for the possibilities of combinations of suture less and mechanical suture in VTLR. Use of VTLR aloe us to minimize the cost of the operation. In the hospital, these methods can be used in closed and video assisted methods in VTLR, but needs further endoscopic electrosealing instruments.